Mefloquine antimalarial prophylaxis in pregnancy: dose finding and pharmacokinetic study. - Nosten, F; Karbwang, J; White, N; Honeymoon; Na Bangchang, K; Bunnag, D; Harinasuta, T (1990)
1. A dose finding pharmacokinetic study was performed in 20 Karen women in the third trimester of pregnancy receiving antimalarial prophylaxis with mefloquine. Ten received 250 mg mefloquine base weekly and ten received identical tablets of 125 mg base/week. 2. Both dose regimens were well tolerated. Malaria was prevented effectively, there were no serious adverse effects, all pregnancies proceeded normally, and there were no abnormalities in the babies followed up to 2 years. 3. The median time from dose administration to peak whole blood mefloquine concentration was 6 (range 3-24) h. Mean (+/- s.d.) peak and trough concentrations in the seventh week were 722 +/- 279 and 488 +/- 155 ng ml-1 with the 250 mg/week dose, and 390 +/- 81 and 185 +/- 53 ng ml-1 with the 125 mg/week dose regimens respectively. These blood concentration values are lower than those reported previously in non-pregnant adults. 4. One and two compartmental models were fitted to the whole blood concentration-time data. Mean (+/- s.d.) clearance (CL/F) was 0.78 +/- 0.27 ml min-1 kg-1, and the apparent terminal elimination half-life (t1/2) was 11.6 +/- 7.9 days. 5. Further studies to determine the oral bioavailability of mefloquine are needed, but these results suggest that clearance may be increased in late pregnancy. These preliminary results of good efficacy without significant toxicity are encouraging, and a more extensive evaluation of mefloquine antimalarial prophylaxis in pregnancy is now warranted.